Protective effect of Onpi-to (TJ-8117) on the expression of apoptosis in 5/6 nephrectomized rats - HATTORI, Tomohisa; FUJITSUKA, Naoki; SHINDO, Shoichiro; KUROGI, Akiko (Nihon Jinzo Gakkai shi, 1997)
The present study was designed to clarify the effects of TJ-8117 on apoptosis in the glomeruli of 5/6 nephrectomized rats. TJ-8117 (400 mg/kg/day), captopril (50 mg/kg/day) and nicardipine (50 mg/kg/day) were administered as drinking water from the 56th day after renal ablation, and continued throughout the experiment. All rats were sacrificed at 13 weeks and renal tissues were removed to quantify histopathological and apoptotic parameters in glomeruli. TJ-8117 inhibited proteinuria, matrix index and decrease in the number of total cells in glomeruli of nephrectomized rats. In addition, the increase in apoptotic body and DNA fragmentation was significantly inhibited in the TJ-8117-treated group. Captopril and nicardipine failed to inhibit both parameters. In 400 mg/kg of the TJ-8117 treated group, the number of Bcl-2 positive cells in the glomeruli was elevated compared with the 5/6 nephrectomized control group. In addition, the number of Bax positive cells in the TJ-8117 group was significantly suppressed in a dosedependent manner. These results suggest that TJ-8117 may inhibit apoptosis in the late stage of this model by suppressing matrix accumulation and progression of glomerulosclerosis. The apoptosis-preventing effect may be mediated by decreased expression of Bax in the glomerular cells.